Effects of 3D-printed exosome-functionalized brain acellular matrix hydrogel on neuroinflammation in rats following cerebral hemorrhage - Aobo Zhang; Boyu Sun; Chengrui Nan; Lulu Cong; Zongmao Zhao; Liqiang Liu (Stem Cell Research & Therapy)
Abstract Background Exosome-based therapeutics have garnered significant attention for intracerebral hemorrhage (ICH) treatment due to their capacity to regulate metabolic dysregulation, restore cellular homeostasis, and modulate the injury microenvironment via bioactive cargoes such as microRNAs and proteins. However, rapid systemic clearance and enzymatic degradation critically limit their therapeutic efficacy. To address this challenge, we engineered a three-dimensional (3D) bioprinted scaffold capable of encapsulating and sustaining the release of human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-exos). Methods Based on previous research [1–3], the scaffold was composed of a decellularized brain matrix (dECM), gelatin-methacryloyl (GelMA), and silk fibroin (SF) crosslinked with a photoinitiator. hUCMSC-exos were precisely incorporated via extrusion-based 3D bioprinting. Release kinetics were assessed via in vitro elution and in vivo imaging. An ICH rat model received stereotaxic implantation of the exosome-laden scaffold (dECM@exo). Neuroinflammatory markers (IL-6, TNF-α, IL-10) and apoptotic activity (JC-1, Annexin V/PI, TUNEL) were quantified. Neurological outcomes were longitudinally evaluated using the modified Longa scale, Bederson scoring, and sensorimotor tests (rotarod, forelimb placement) at 1, 4, 7 and 14 days post-ICH. Results dECM@exo demonstrated sustained exosome release over 14 days, significantly promoting neural tissue regeneration while attenuating perihematomal edema. Mechanistically, the scaffold modulated pathological MMP activity and inflammatory cytokine expression, thereby restoring extracellular matrix homeostasis and reducing neuronal apoptosis. Conclusions The findings demonstrate that the 3D biological scaffold dECM@exo effectively maintains microenvironmental homeostasis in the early stages of ICH and improves outcomes associated with the condition. dECM@exo is poised to serve as a robust platform for drug delivery and biotherapy in ICH treatment, offering a viable alternative for managing this condition.